Modified lithium manganese iron phosphate positive electrode material and preparation method and application thereof

By doping rare earth elements Yb or Eu into the lithium manganese iron phosphate positive electrode material and carbon coating, the chemical environment of Mn3+ electron cloud in the MnO6 octahedral is adjusted, and the problem of poor capacity attenuation and cycle stability of the positive electrode material at high magnification is solved. Excellent electrochemical performance and cycle stability at high magnifications are achieved.

CN119208578BActive Publication Date: 2025-02-25TIANJIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411698083.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials show the problems of capacity attenuation and poor cycle stability at high magnification, and it is difficult to meet the electrochemical performance and cycle stability at high magnification at both.

Method used

Through the doping and carbon coating technology of rare earth elements Yb or Eu, the chemical environment of Mn3+ electron cloud in MnO6 octahedral is adjusted to reduce the Jahn-Teller distortion effect, thereby improving the rate performance and cycle stability of the cathode material.

Benefits of technology

It achieves a high discharge specific capacity and excellent capacity retention rate at high magnification (5.0C~10.0C), which improves the overall electrochemical performance and cycle stability of the cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208578B_ABST
    Figure CN119208578B_ABST
Patent Text Reader

Abstract

The present invention provides a modified lithium iron manganese phosphate positive electrode material and a preparation method and application thereof, belonging to the field of electrodes and lithium ion batteries. The modified lithium iron manganese phosphate positive electrode material is a carbon-coated modified lithium iron manganese phosphate, wherein the modified lithium iron manganese phosphate is LiMn 0.6 Fe 0.4‑x M x PO4, 0.005≤x≤0.02, M is Yb or Eu.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of electrodes and lithium-ion batteries, and particularly relates to a modified lithium manganese iron phosphate cathode material, a preparation method and an application thereof, and more specifically relates to a modified lithium manganese iron phosphate cathode material, a preparation method thereof, a positive electrode sheet and a lithium-ion battery using the modified lithium manganese iron phosphate cathode material. Background Art

[0002] As an efficient energy storage and conversion device, lithium-ion batteries are widely used in the new energy field.

[0003] Lithium iron phosphate (LiFePO4) has advantages such as strong thermal stability, high safety performance, no noble metals other than lithium, and low price compared with traditional layered cathode materials (such as lithium cobaltate and lithium nickelate). Therefore, the LiFePO4 cathode material is widely used as the positive electrode sheet of lithium-ion batteries and its market share increases year by year. However, the LiFePO4 cathode material has disadvantages such as low energy density and poor low-temperature performance, which also restrict its further application.

[0004] To further develop higher-performance cathode materials, the research on lithium manganese phosphate (LiMnPO4) cathode materials with the same olivine structure as LiFePO4 (capacity retention rate nearly 48% at -20°C low temperature) has begun. The LiMnPO4 cathode material has excellent low-temperature performance (capacity retention rate nearly 80% at -20°C low temperature) and a high voltage platform of ~4.1V, and the theoretical energy density is as high as 701 Wh / kg, which is about 20% higher than that of LiFePO4. Therefore, in order to improve the electrochemical performance of LiFePO4, it is proposed to partially replace the Fe element in the lattice of the LiFePO4 cathode material with manganese (Mn) element to obtain a lithium manganese iron phosphate (LiMn y Fe y PO4, 0 < y < 1) cathode material. This cathode material combines the advantages of LiFePO4 and LiMnPO4 and has greater development potential in the field of lithium-ion batteries in the future. However, for the LiMn 1-y Fe y PO4 cathode material, due to the double degeneracy of the outermost electron layer e 3+ orbital of Mn g the electron cloud system of Mn 3+ is in a metastable state, resulting in the structural disorder of MnO6 and the Jahn-Teller effect, which easily causes lattice mismatch and structural distortion of the LiMn 1-y Fe y PO4 cathode material, thereby leading to poor rate performance and cycle stability of the material, especially significant capacity attenuation occurs during charge and discharge at high rates (10.0C).

[0005] In order to suppress the LiMn 1-y Fe y The Jahn-Teller effect of PO4 positive electrode materials improves their stability. Currently, strategies such as surface carbon coating, particle nano-sizing and metal ion doping have been proposed to regulate and modify the materials. However, these strategies are difficult to simultaneously meet the requirements of higher electrochemical performance and cycle stability at higher rates. Summary of the Invention

[0006] In view of this, the present invention proposes a modified lithium manganese iron phosphate cathode material and its preparation method and application, in order to at least partially solve the above technical problems. Therefore, the technical solution provided by the present invention is as follows.

[0007] As a first aspect of the present invention, a modified lithium iron manganese phosphate positive electrode material is provided. The modified lithium iron manganese phosphate positive electrode material is a carbon-coated modified lithium iron manganese phosphate, wherein the modified lithium iron manganese phosphate is LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu.

[0008] As a second aspect of the present invention, a method for preparing a modified lithium iron manganese phosphate positive electrode material is provided, comprising: providing FePO4 nanoparticles; ball-milling and mixing a solvent, FePO4 nanoparticles, a lithium source, a manganese source, a phosphorus source, a carbon source and an M source to form a slurry, wherein the M source is a Yb source or an Eu source; drying, grinding and sieving the slurry to obtain a powder; and calcining the powder in an inert atmosphere in stages to obtain a modified lithium iron manganese phosphate positive electrode material, wherein the modified lithium iron manganese phosphate positive electrode material is a carbon-coated modified lithium iron manganese phosphate.

[0009] As a third aspect of the present invention, a positive electrode sheet is provided, which is composed of a positive electrode collector and a positive electrode slurry coated and solidified on the surface of the positive electrode collector, wherein the positive electrode slurry includes the above-mentioned modified lithium manganese iron phosphate positive electrode material, a conductive material, a binder and an organic solvent.

[0010] As a fourth aspect of the present invention, a lithium-ion battery is provided, wherein the lithium-ion battery adopts the above-mentioned positive electrode sheet.

[0011] In the embodiment of the present invention, the unique non-spherical flexible 4f electron orbital and the tendency to absorb foreign localized electrons of Yb or Eu rare earth metal ions are used to adjust the MnO6 octahedron. 3+ The electrochemical environment of the electron cloud reduces the 0.6 Fe 0.4-x M xThe Jahn-Teller distortion effect of PO4 is reduced, thereby reducing the structural distortion of the positive electrode material. Therefore, a Yb or Eu rare earth element doped carbon-coated lithium manganese iron phosphate positive electrode material with higher rate performance and excellent cycle stability is designed. The present invention uses a solid phase mixing method to utilize rare earth element doped carbon-coated lithium manganese iron phosphate (LiMn 1- y Fe y PO4), obtain modified lithium manganese iron phosphate positive electrode material (LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu). The present invention improves the electronic conductivity of the modified lithium manganese iron phosphate positive electrode material through carbon coating and rare earth element doping. In addition, the carbon coating can effectively prevent the positive electrode from directly contacting the electrolyte, reduce the occurrence of some side reactions, and improve its cycle stability.

[0012] In the embodiment of the present invention, spherical FePO4 nanoparticles with high dispersibility and uniform particle size distribution are used as the raw materials for synthesizing modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.4-x M x The iron source precursor of the positive electrode material of lithium manganese iron phosphate is obtained by mixing FePO4 nanoparticles with lithium source, manganese source, phosphorus source, carbon source, Yb or Eu rare earth metal, and calcining to obtain a spherical, uniformly sized carbon-coated modified lithium manganese iron phosphate positive electrode material. The method for synthesizing the positive electrode material is relatively simple and can be prepared in batches. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a scanning electron microscope (SEM) image of the FePO4 nanoparticles in Example 1 of the present invention;

[0014] Figure 2 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 X-ray diffraction (XRD) pattern of PO4-S1 cathode material;

[0015] Figure 3 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 SEM image of PO4-S1 cathode material;

[0016] Figure 4 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cycling stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 5.0C;

[0017] Figure 5 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cycling stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 10.0C;

[0018] Figure 6 LiMn in Example 5 of the present invention 0.6 Fe 0.39 Yb 0.01 SEM image of PO4-S5 cathode material;

[0019] Figure 7 LiMn in Comparative Example 1 0.6 Fe 0.4 SEM image of PO4-S6 cathode material;

[0020] Figure 8 This is the SEM image of FePO4 nanoparticles in Comparative Example 2. DETAILED DESCRIPTION

[0021] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concept of the present invention.

[0022] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0023] In the case of using expressions such as "at least one of A, B, and C, etc.", generally, it should be interpreted according to the meaning that those skilled in the art usually understand this expression (for example, "a system having at least one of A, B, and C" should include, but not be limited to, a system having only A, only B, only C, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", generally, it should be interpreted according to the meaning that those skilled in the art usually understand this expression (for example, "a system having at least one of A, B, or C" should include, but not be limited to, a system having only A, only B, only C, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.).

[0024] To suppress the Jahn-Teller effect of the LiMn 1-y Fe y PO4 (0 < y < 1) cathode material and improve its stability, currently, strategies such as surface carbon coating, particle nanosizing, and metal ion doping are proposed to regulate and modify the material, but there are some problems with these strategies.

[0025] For example: In the prior art, lithium iron phosphate doped with rare earth elements (any one of La, Ce, Pr, Tb, Sm) and carbon-coated is used to improve the lattice defects of the cathode material, and the stability of the crystal structure of the cathode material is improved. Although the cycle stability of the obtained cathode material has a certain improvement at a low rate (0.1C), the discharge specific capacity is relatively low, that is, the discharge specific capacity at 0.1C is only 116 - 120.0 mAh / g.

[0026] For example: Using metal ions (any one of Ti, Mg, V) to dope lithium iron phosphate with secondary carbon coating, through the strategy of ion doping modification combined with secondary carbon coating, the electron and ion transport efficiency between material particles is optimized, but the discharge specific capacity of this cathode material at a higher rate is still poor.

[0027] For another example: Using manganese element to dope and modify lithium iron phosphate material to obtain a carbon-coated modified lithium manganese iron phosphate cathode material. By using the synergistic effect of the gradient distribution of manganese, carbon, and iron elements, while reducing manganese loss, the electron conductivity is enhanced. However, the discharge specific capacity of this cathode material at 1.0C is 126.1 - 142 mAh / g, and the preparation process of this cathode material is relatively cumbersome, and dispersants and complexing agents are also added, and the subsequent treatment is complex, resulting in high production costs.

[0028] For example, in the prior art, there are also modified lithium manganese iron phosphate cathode materials doped with different elements (at least one of La and Al). By bulk doping, the Li-O bond is extended and vacancies are formed, which facilitates the Li + Migration and stabilization of the material structure improve electrochemical performance. However, the discharge capacity and capacity retention of the prepared cathode material at a low rate of 1.0C need to be further improved.

[0029] Another example is the cathode material obtained by doping and modifying lithium manganese iron phosphate with at least one metal element selected from Ti, V, Ni, and Mg. The prepared manganese iron hydroxide is mainly in the form of burred particles with tight internal connections, which can effectively alleviate the problem of easy breakage of spherical particles during sintering, thereby making the prepared cathode material have a higher energy density. Although the discharge specific capacity of this cathode material is improved at a low rate (1.0C), such as the capacity retention rate of 80% to 91.5% after 100 cycles at 1.0C, the discharge specific capacity is low at higher rates, and the capacity retention rate is low after long cycles.

[0030] Another example is the carbon-coated lithium manganese iron phosphate cathode material. By adding a modifier during the slurry pretreatment process to promote the self-assembly of the raw materials into a precursor, and then coating the precursor with carbon, the conductivity of the lithium manganese iron phosphate material is improved. Although the resulting cathode material has a significant improvement in conductivity, further verification is needed to verify the battery's rate performance and cycle performance.

[0031] Another example is the use of fluorine-doped lithium manganese iron phosphate cathode materials coated with amorphous carbon and graphene. By constructing a conductive network and doping with F ions to form F-Mn chemical bonds, manganese loss is reduced, while conductivity and structural stability are improved. Although the resulting material shows improved discharge capacity and battery capacity retention at a lower rate (0.1C), performance is poor at higher rates (>1.0C). Furthermore, the use of N,N-dimethylformamide as a solvent is not only expensive but also highly polluting, making it unsuitable for large-scale factory production.

[0032] Another example: By adjusting the particle size ratio of the material, a lithium manganese iron phosphate positive electrode material is obtained. Although this positive electrode material has excellent discharge specific capacity at a lower rate (0.1C), its electrochemical performance at a high rate (10.0C) needs to be further improved, and the battery cycle stability also needs further exploration.

[0033] Another example: In existing technology, lithium manganese iron phosphate cathode materials are prepared by in-situ growing lithium manganese iron phosphate on the surface of conductive carbon microspheres to form a three-dimensional conductive network to improve the material's conductivity. This process is then combined with freeze-drying to stabilize the material structure. While this method exhibits improved discharge capacity (128.5 mAh / g) at a low rate (0.1C), the capacity at a high rate (10.0C) decreases significantly (41.0 mAh / g). Furthermore, the preparation process is complex, making it unsuitable for industrial applications.

[0034] To address the difficulties encountered in the prior art in simultaneously achieving both high-rate (10.0C) electrochemical performance and cycle stability, the present invention proposes utilizing rare earth element-doped carbon-coated lithium manganese iron phosphate to produce a modified lithium manganese iron phosphate cathode material. By utilizing the unique aspherical, flexible 4f electron orbitals and tendency to absorb external, localized electrons of the rare earth elements Yb and Eu, structural distortion in the cathode material is reduced, resulting in the modified lithium manganese iron phosphate cathode material achieving higher rate performance and cycle stability.

[0035] Specifically, as the first aspect of the present invention, the modified lithium manganese iron phosphate positive electrode material provided by the present invention is a carbon-wrapped modified lithium manganese iron phosphate, wherein the modified lithium manganese iron phosphate is LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu.

[0036] In the embodiment of the present invention, Eu 3+ 、Yb 3+ Rare earth metal ions have unique non-spherical flexible 4f electron orbitals, where the anisotropic shape of the 4f electron orbital electron cloud originates from the spin-orbit coupling caused by the staggered orbital energy levels of rare earth metal ions. 3+ 、Yb 3+ The outermost electron layer in the rare earth metal ions has the characteristic of tending to absorb foreign localized electrons to achieve a more stable state of half-filled or fully filled electron layer. 3+ 、Yb 3+ The aspherical flexible 4f electron orbital characteristics of rare earth metal ions and their tendency to absorb foreign localized electrons are used to adjust the Mn in the MnO6 octahedron. 3+ The chemical environment of the electron cloud can reduce the 0.6 Fe 0.4-x M x Jahn-Teller distortion of PO4. The Jahn-Teller effect is significantly suppressed, thereby reducing the structural distortion of the positive electrode material, thereby obtaining a rare earth element-doped carbon-coated lithium manganese iron phosphate positive electrode material with higher rate performance and excellent cycle stability.

[0037] According to embodiments of the present invention, the modified lithium manganese iron phosphate has an olivine structure, wherein Fe is in a +2 valence state, and Mn and M (M is Yb or Eu) both have a +3 valence state. This olivine-structured modified lithium manganese iron phosphate offers advantages such as strong thermal stability, high safety, the absence of precious metals other than lithium, and low cost.

[0038] According to an embodiment of the present invention, as a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned modified lithium iron manganese phosphate positive electrode material, comprising: providing FePO4 nanoparticles as an iron source; ball-milling and mixing a solvent, FePO4 nanoparticles, a lithium source, a manganese source, a phosphorus source, a carbon source and an M source to form a slurry, wherein the M source is a Yb source or a Eu source; the slurry is dried, ground and sieved to obtain a powder; and the powder is calcined in an inert atmosphere to obtain a carbon-coated modified lithium iron manganese phosphate positive electrode material.

[0039] In an embodiment of the present invention, spherical FePO4 nanoparticles with high dispersibility, uniform particle size and uniform distribution are used as the iron source for synthesizing the modified lithium manganese iron phosphate positive electrode material, and then the FePO4 nanoparticles are mixed with a lithium source, a manganese source, a phosphorus source, a carbon source, and an M source (i.e., Yb or Eu rare earth element) by ball milling. After calcination, a spherical, uniform particle size and uniform distribution carbon-coated modified lithium manganese iron phosphate positive electrode material can be obtained. The method for synthesizing the positive electrode material is relatively simple, does not use additional additives, has low cost, simple post-processing process, and can be prepared in batches.

[0040] According to an embodiment of the present invention, FePO4 nanoparticles are prepared by the following method: under oxidant conditions, an oxidation reaction is first carried out with a divalent iron salt and a phosphorus-containing solution, and then the pH of the reaction solution is adjusted to 1.5-1.8 with an alkaline solution, and the reaction is carried out for 1-3 hours to obtain a FePO4 slurry, and the FePO4 slurry is calcined at 500-550°C for 2-3 hours to obtain FePO4 nanoparticles, wherein the phosphorus-containing solution includes a phosphate solution or a phosphoric acid solution. The divalent iron salt is selected from FeSO4·7H2O, and for other Fe 2+ A divalent iron salt can also be used; the phosphate is selected from at least one of sodium phosphate and sodium dihydrogen phosphate; and the alkali solution is selected from either NaOH or KOH, preferably NaOH. For example, the preparation of FePO4 nanoparticles includes: dissolving a divalent iron salt (FeSO4·7H2O) in pure water as a base liquid, pouring a phosphoric acid solution into the base liquid under continuous stirring, and adding a hydrogen peroxide solution dropwise using a constant pressure dropping funnel to oxidize the Fe 2+The temperature was then raised to 80°C, and the pH was adjusted to 1.8 using a NaOH solution. The reaction was continued in an oil bath with constant stirring for 3 hours. The slurry was then filtered while still hot to obtain a FePO4 precipitate. This was washed with pure water and filtered five times. The product was then dried and calcined to obtain white FePO4 nanoparticles.

[0041] According to an embodiment of the present invention, the lithium source is selected from at least one of Li2CO3, LiOH, LiNO3, LiCl, and CH3COOLi; the manganese source is selected from at least one of MnCO3, Mn3(PO4)2, MnHPO4, Mn(H2PO4)2, Mn(CH3COO)2, Mn(NO3)2, MnSO4, MnC2O4, and MnCl2; the phosphorus source is selected from at least one of H3PO4, Fe3(PO4)2, FePO4, (NH4)2HPO4, NH4H2PO4, (NH4)3PO4, Li3 PO4, LiH2PO4; the carbon source is selected from at least one of glucose, sucrose, fructose, soluble starch, citric acid, amino acid, dextrin, polyvinyl pyrrolidone, and polyethylene glycol; the Yb source is selected from any one of Yb2O3, Yb(CH3COO)3·4H2O, YbCl3, Yb2(SO4)3, and Yb(NO3)3·5H2O; the Eu source is selected from any one of Eu2O3, Eu(CH3COO)3·4H2O, EuCl3, Eu2(SO4)3, and Eu(NO3)3·6H2O.

[0042] According to an embodiment of the present invention, the ball milling mixing time is 6 to 15 hours, the rotation speed is 600 to 1000 rpm, and the ball-to-material ratio is 15 to 20:1. Within this ratio range, it is helpful to evenly mix the FePO4 nanoparticles, lithium source, manganese source, phosphorus source, carbon source and M source (i.e., Yb source or Eu source) by ball milling, so that the subsequent calcination can obtain a modified lithium manganese iron phosphate positive electrode material with a spherical shape, uniform particle size and uniform distribution.

[0043] According to an embodiment of the present invention, the powder is calcined in stages, including first calcining the powder at 300-350°C for 2-6 hours, and then calcining it at 600-750°C for 10-15 hours. The first stage effectively removes excess moisture from the powder, preventing particle breakage caused by excessive temperatures during calcination. The second stage removes excess impurities from the powder and simultaneously activates it.

[0044] According to an embodiment of the present invention, a positive electrode sheet is provided. The positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated and cured on the positive electrode current collector. The positive electrode slurry comprises the modified lithium manganese iron phosphate positive electrode material, a conductive agent, a binder, and an organic solvent. The positive electrode current collector is selected from aluminum foil; the conductive agent is selected from any one of conductive carbon black (Super P), acetylene black, Ketjen black, and carbon nanotubes; the binder is selected from any one of polyvinylidene fluoride, polystyrene butadiene copolymer, sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, polyamide, polyethyleneimine, and polypyrrole; and the organic solvent is selected from any one of N-methylpyrrolidone, dimethylformamide, and dimethyl sulfoxide.

[0045] In an embodiment of the present invention, a modified lithium manganese iron phosphate positive electrode material, a conductive agent, a binder and an organic solvent are mixed to form a positive electrode slurry, which is then coated on a positive electrode collector to form a positive electrode sheet. The obtained positive electrode sheet has high electrochemical performance.

[0046] According to an embodiment of the present invention, the present invention further provides a lithium-ion battery, which uses the positive electrode sheet in the above embodiment.

[0047] According to an embodiment of the present invention, the lithium-ion battery may be a button battery.

[0048] In an embodiment of the present invention, the modified lithium manganese iron phosphate positive electrode material provided by the present invention has a lithium ion battery composed of a high discharge specific capacity and a good capacity retention rate at 0.1C~10.0C, especially at a high rate of 5.0C~10.0C.

[0049] In order to make the technical solution of the present invention clearer and more understandable, the technical solution of the present invention is described in detail below with reference to specific embodiments and drawings. It should be noted that the following specific embodiments are only examples.

[0050] Example

[0051] Example 1

[0052] Preparation of FePO₄ nanoparticles: First, 69.52 g of FeSO₄·7H₂O and 200 mL of pure water were added to a 1000 mL three-necked flask to form a solution. Then, 30.00 g of an 85% H₃PO₄ solution was added dropwise to the flask under magnetic stirring at 1000 r / min. After the addition, the mixture was stirred for 2 minutes to obtain a mixed solution. Next, 17.00 g of a 30% H₂O₂ solution was added dropwise to the mixed solution at a rate of 1 drop / second. Furthermore, 50 mL of a 6.66 mol / L NaOH solution was added dropwise to the flask in an 80°C oil bath at a rate of 1 drop / second. After the addition, the reaction was continued for 3 hours. The solid FePO₄ sample was then separated by hot filtration. Subsequently, the sample was washed with 500 mL of pure water at 200 r / min with stirring for 3 minutes, filtered, and the washing process repeated three times. Finally, the anhydrous FePO4 nanoparticles were obtained by calcining at 550 °C in a tube furnace in air atmosphere for 3 h.

[0053] Figure 1 This is a scanning electron microscope (SEM) image of the FePO4 nanoparticles in Example 1 of the present invention.

[0054] like Figure 1 As shown, the FePO4 nanoparticles synthesized by the method in Example 1 have a regular spherical morphology, a smooth surface, and uniform particle size and distribution.

[0055] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1 (LMFP-1%Yb) cathode material: 11.90 g of the prepared FePO4 nanoparticles (iron source), 3.37 g of Li2CO3, 13.97 g of MnCO3, 12.63 g of LiH2PO4, 0.71 g of Yb(CH3COO)3·4H2O, and 10.65 g of glucose were weighed and mixed with 66.54 mL of distilled water in a 500 mL beaker. The mixture was then ball milled at 800 rpm for 12 h at a ball-to-material ratio of 15:1. After ball milling, the mixture was dried at 80°C for 12 h and dry-milled at 1000 rpm for 20 min to obtain the precursor sample. Finally, the precursor sample was placed in a tube furnace and calcined at 350 °C for 4 h under nitrogen atmosphere and then at 670 °C for 12 h to obtain LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode material.

[0056] Figure 2 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 X-ray diffraction (XRD) pattern of PO4-S1 cathode material.

[0057] like Figure 2 As shown, the LiMn synthesized in Example 1 0.6 Fe 0.39 Yb 0.01 The XRD spectrum of the PO4-S1 cathode material sample is similar to the spectrum and diffraction data of the lithium manganese iron phosphate standard card (PDF#13-0336), with a sharp peak shape, indicating that the cathode material has good crystallinity, and no other impurity peaks are observed in the spectrum, indicating that the LiMn prepared by the method provided by the present invention is 0.6 Fe 0.39 Yb 0.01 The PO4-S1 cathode material is pure phase LMFP.

[0058] Figure 3 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 SEM image of PO4-S1 positive electrode material.

[0059] like Figure 3 As shown, the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The particle size distribution of PO4-S1 positive electrode material is uniform and the dispersion is good.

[0060] Preparation of LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode sheet: First, weigh 0.1g of polyvinylidene fluoride (PVDF) as a binder and add it to a weighing bottle. Then, add 1.5mL of N-methylpyrrolidone (NMP) organic solvent to the weighing bottle and stir magnetically at 1000rpm / min for 2h. Then, add 0.8g of the prepared LiMn 0.6 Fe 0.39 Yb 0.01PO4-S1 positive electrode material, 0.1g conductive agent (Super P) and 2mL NMP were added to the above-mentioned weighing bottle and magnetically stirred at 1000rpm / min for 4h to obtain positive electrode slurry. Subsequently, the positive electrode slurry was evenly coated on aluminum foil using a coating machine at a coating speed of 25mm / s to a coating thickness of 150μm. The coated aluminum foil was then placed in a 60℃ forced air drying oven to dry for 4h; thereafter, it was sheeted and dried in a vacuum oven at 110℃ for 12h to obtain LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode sheet.

[0061] Assemble button cells: In a glove box, 0.6 Fe 0.39 Yb 0.01 The PO4-S1 positive electrode sheet is used as the working electrode, metallic lithium is used as the counter electrode, Celgard2400 is used as the separator, and 1 mol / L LiPF6 / EC:DEC:DMC (volume ratio 1:1:1) is used as the electrolyte, and they are assembled into a CR2032 button battery.

[0062] The charge and discharge performance test of the button battery was carried out. The specific test process was as follows: under constant current conditions at room temperature, the test voltage range of rate performance was 2.5V to 4.5V, the charge and discharge rate was 0.1C for 3 cycles, 0.2C, 0.5C, 1.0C, 2.0C, 5.0C, and 10.0C for 5 cycles each, and then back to 0.1C for 5 cycles. The specific test results are shown in Table 1.

[0063] After testing, it can be seen from Table 1 that LiMn 0.6 Fe 0.39 Yb 0.01 The PO4-S1 positive electrode sheet has a first discharge specific capacity of 155.80 mAh / g at 0.1C; the first discharge specific capacity at 0.2C is 153.76 mAh / g; the first discharge specific capacity at 0.5C is 150.75 mAh / g; the first discharge specific capacity at 1.0C is 146.14 mAh / g; the first discharge specific capacity at 2.0C is 143.45 mAh / g; the first discharge specific capacity at 5.0C is 135.32 mAh / g; and the first discharge specific capacity at 10.0C is 127.73 mAh / g.

[0064] Furthermore, the LiMn 0.6 Fe 0.39 Yb 0.01 The battery composed of PO4-S1 positive electrode sheets was tested for cycle stability at different rates. The specific test results Figure 4-Figure 5 and as shown in Table 2.

[0065] Figure 4 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cycling stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 5.0C; Figure 5 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cycling stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 10.0C.

[0066] like Figure 4 As shown in Figure 2, after 500 cycles at 5.0C, the battery capacity retention rate is 93.32%; Figure 5 As shown in the figure, after 500 cycles at 10.0C, the battery capacity retention rate is 93.44%. 0.6 Fe 0.39 Yb 0.01 The PO4-S1 cathode material has high rate performance at low rate (0.1C), no obvious attenuation of specific capacity at 5.0C, and stable electrochemical performance at high rate (10.0C).

[0067] Example 2

[0068] Preparation of FePO₄ nanoparticles: First, 69.52g of FeSO₄·7H₂O and 200mL of pure water were added to a 1000mL three-necked flask to form a solution. Then, 30.00g of an 85% H₃PO₄ solution was added dropwise to the three-necked flask under magnetic stirring at 1000 r / min. After the addition, the mixture was stirred for 2 minutes to obtain a mixed solution. Next, 17.00g of a 30% H₂O₂ solution was added dropwise to the mixed solution at a rate of 1 drop / second. Finally, 50mL of a 6.66mol / L NaOH solution was added dropwise to the three-necked flask in an 80°C oil bath at the same rate of 1 drop / second. After the addition, the reaction was continued for 3 hours. The hot FePO₄ solid sample was separated by suction filtration and washed with 500mL of pure water at 200 r / min for 3 minutes, followed by suction filtration. This washing process was repeated three times. Finally, the anhydrous FePO4 nanoparticles were obtained by calcining at 550 °C in a tube furnace in air atmosphere for 3 h.

[0069] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.395 Yb 0.005PO4-S2) positive electrode material: The masses of the FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Yb(CH3COO)3·4H2O and glucose prepared above were weighed as 12.01g, 3.37g, 13.97g, 12.63g, 0.35g and 10.65g, respectively, and mixed evenly with 66.54mL of distilled water in a 500mL beaker. Then, the mixture was ball-milled at 800rpm for 12h with a ball-to-material ratio of 15:1. After ball milling, the mixture was dried with forced air at 80°C for 12h and dry-milled at 1000rpm for 20min to obtain a precursor sample. Finally, the precursor sample was placed in a tube furnace and calcined at 350°C for 4h under nitrogen atmosphere, and then calcined at 670°C for 12h to obtain LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode material.

[0070] Preparation of LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode sheet: First, weigh 0.1g of polyvinylidene fluoride (PVDF) as a binder and add it to a weighing bottle. Then, add 1.5mL of N-methylpyrrolidone (NMP) organic solvent to the weighing bottle and stir magnetically at 1000rpm / min for 2h. Then, add 0.8g of the prepared LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode material, 0.1g Super P and 2mL NMP were added to the above-mentioned weighing bottle and magnetically stirred at 1000rpm / min for 4h to obtain positive electrode slurry. Subsequently, the positive electrode slurry was evenly coated on aluminum foil using a coating machine at a coating speed of 25mm / s to a coating thickness of 150μm. The coated aluminum foil was then placed in a blast drying oven at 60℃ and dried for 4h; thereafter, it was sheeted and dried in a vacuum oven at 110℃ for 12h to obtain LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode sheet.

[0071] Assemble button cells: In a glove box, 0.6 Fe 0.395 Yb 0.005 The PO4-S2 positive electrode sheet was used as the working electrode, metallic lithium was used as the counter electrode, Celgard2400 was used as the separator, and 1 mol / L LiPF6 / EC:DEC:DMC (volume ratio 1:1:1) was used as the electrolyte, and they were assembled into a CR2032 button cell.

[0072] The charge and discharge performance test of the button cell was conducted. The specific test process was as follows: under constant current conditions at room temperature, the test voltage range of rate performance was 2.5V to 4.5V, the charge and discharge rate was 0.1C for 3 cycles, 0.2C, 0.5C, 1.0C, 2.0C, 5.0C, 10.0C for 5 cycles each, and then back to 0.1C for 5 cycles. 0.6 Fe 0.395 Yb 0.005 The battery composed of PO4-S2 positive electrode sheets was tested for cycle stability at different rates. The specific test results are shown in Tables 1 and 2.

[0073] After testing, it can be seen from Table 1 that LiMn 0.6 Fe 0.395 Yb 0.005 The PO4-S2 positive electrode sheet has an initial discharge capacity of 155.12 mAh / g at 0.1C, 151.61 mAh / g at 0.2C, 148.65 mAh / g at 0.5C, 144.79 mAh / g at 1.0C, 140.22 mAh / g at 2.0C, 133.24 mAh / g at 5.0C, and 124.01 mAh / g at 10.0C. 0.6 Fe 0.395 Yb 0.005 The PO4-S2 positive electrode sheet has a battery capacity retention rate of 91.94% after 500 cycles at 5.0C; and a battery capacity retention rate of 91.86% after 500 cycles at 10.0C.

[0074] Example 3

[0075] Preparation of FePO4 nanoparticles: Example 3 uses the same method as in Examples 1 and 2 to prepare anhydrous FePO4 nanoparticles.

[0076] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.38 Yb 0.02PO4-S3) positive electrode material: The FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Yb(CH3COO)3·4H2O and glucose prepared above were weighed to 11.60g, 3.37g, 13.97g, 12.63g, 1.42g and 10.65g respectively, and mixed evenly with 66.54mL of distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was carried out at 800rpm for 12h; after ball milling, the mixture was dried with forced air at 80℃ for 12h and dry milled at 1000rpm for 20min to obtain a precursor sample. Finally, the precursor sample was placed in a tube furnace and calcined at 350℃ for 4h under nitrogen atmosphere, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.38 Yb 0.02 PO4-S3 positive electrode material.

[0077] Example 3: LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.38 Yb 0.02 PO4-S3 positive electrode sheets were assembled into button batteries for charge and discharge performance and battery cycle stability tests at different rates. The specific test process was the same as that of Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0078] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.38 Yb 0.02 The PO4-S3 positive electrode sheet has an initial discharge capacity of 154.74 mAh / g at 0.1C, 151.19 mAh / g at 0.2C, 148.84 mAh / g at 0.5C, 145.88 mAh / g at 1.0C, 141.92 mAh / g at 2.0C, 133.99 mAh / g at 5.0C, and 125.99 mAh / g at 10.0C. 0.6 Fe 0.38 Yb 0.02 The PO4-S3 positive electrode sheet was cycled for 500 cycles at 5.0C, and the battery capacity retention rate was 92.84%; after cycling for 500 cycles at 10.0C, the battery capacity retention rate was 93.17%.

[0079] Example 4

[0080] Preparation of FePO4 nanoparticles: Example 4 uses the same method as in Examples 1 and 2 to prepare anhydrous FePO4 nanoparticles.

[0081] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Eu 0.01 PO4-S4) positive electrode material: The FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Eu(CH3COO)3·4H2O and glucose prepared above were weighed to 11.90g, 3.37g, 13.97g, 12.63g, 0.71g and 10.65g respectively, and mixed evenly with 66.54mL of distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was carried out at 800rpm for 12h; after ball milling, it was blown dried at 80℃ for 12h and dry milled at 1000rpm for 20min to obtain a precursor sample. Finally, the precursor sample was placed in a tube furnace and calcined at 350℃ for 4h under nitrogen atmosphere, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.39 Eu 0.01 PO4-S4 positive electrode material.

[0082] LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.39 Eu 0.01 PO4-S4 positive electrode sheets were assembled into button batteries for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process was the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0083] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.39 Eu 0.01 The PO4-S4 positive electrode sheet has an initial discharge capacity of 150.73 mAh / g at 0.1C, 146.72 mAh / g at 0.2C, 143.99 mAh / g at 0.5C, 140.14 mAh / g at 1.0C, 137.77 mAh / g at 2.0C, 132.62 mAh / g at 5.0C, and 124.52 mAh / g at 10.0C. 0.6 Fe 0.39 Eu 0.01 The PO4-S4 positive electrode sheet was cycled for 500 cycles at 5.0C, and the battery capacity retention rate was 93.84%; after cycling for 500 cycles at 10.0C, the battery capacity retention rate was 93.10%.

[0084] Example 5

[0085] Preparation of FePO4 nanoparticles: FePO4 nanoparticles were prepared using the method provided in Chinese Patent Publication No. CN114477120A (A method for preparing iron phosphate). Specifically, 25 mL of FeSO4·7H2O solution was added to a 100 mL reactor, the temperature was raised to 40°C, stirred at 50 rpm, and a flow rate of 13 m 3 / h H3PO4 solution, after 3 hours of reaction, add excess H2O2 solution to the reaction system Fe 2+ Oxidized to Fe 3+ The oxidation reaction was continued for 2 hours. After the reaction, the pH of the reaction system was adjusted to 4.2 with NH3·H2O solution, producing a milky white precipitate. The temperature was then raised to 90°C and stirred for 1.0 hour. After the reaction was complete, the solid was filtered while hot. After filtration, the solid was placed in a 1000mL beaker, 500ml of pure water was added, and stirred with an electric stirrer at 200 rpm for 3 minutes. This was the first filtration and washing. The filtration and washing process was repeated five times. After washing, the solid was transferred to a large glass Petri dish and placed in a forced air drying oven at 60°C. It was then dried at this temperature for 12 hours. Finally, the sample was placed in a quartz boat in a tube furnace and heated in air at a rate of 5°C / min to 550°C. It was then calcined in the tube furnace at this temperature for 3 hours to produce anhydrous FePO4 nanoparticles.

[0086] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S5) positive electrode material: Li2CO3, the above-mentioned FePO4 nanoparticles, MnCO3, LiH2PO4, Yb(CH3COO)3·4H2O, and glucose were weighed as 3.37g, 11.90g, 13.97g, 12.63g, 0.71g, and 10.65g respectively; then 66.22mL of distilled water was added; with a ball-to-material ratio of 15:1, the mixture was ball-milled at 800rpm for 12h; then the mixture was dried with air at 80℃ to evaporate all the water, and after evaporation, it was dry-milled at 1000rpm for 20min; then the powder was sieved through a 200-mesh standard sieve to obtain a precursor sample. The precursor powder was placed in a nitrogen atmosphere, first calcined at 350℃ for 4h, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S5 positive electrode material.

[0087] Figure 6 LiMn in Example 5 of the present invention 0.6 Fe 0.39 Yb 0.01SEM image of PO4-S5 cathode material.

[0088] like Figure 6 As shown, the LiMn prepared in Example 5 0.6 Fe 0.39 Yb 0.01 The PO4-S5 cathode material has a large particle size, poor dispersion, and severe agglomeration. This suggests that the particle size and dispersion of the FePO4 nanoparticle precursor will affect the particle size and distribution of the cathode material.

[0089] Example 5: LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.39 Yb 0.01 PO4-S5 positive electrode sheets were assembled into button batteries for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing processes were the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0090] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.39 Yb 0.01 The PO4-S5 positive electrode sheet has an initial discharge capacity of 144.20 mAh / g at 0.1C, 142.72 mAh / g at 0.2C, 141.26 mAh / g at 0.5C, 139.95 mAh / g at 1.0C, 136.32 mAh / g at 2.0C, 121.26 mAh / g at 5.0C, and 106.47 mAh / g at 10.0C. 0.6 Fe 0.39 Yb 0.01 The PO4-S5 positive electrode sheet was cycled for 500 cycles at 5.0C, and the battery capacity retention rate was 92.50%; after cycling for 500 cycles at 10.0C, the battery capacity retention rate was 93.10%.

[0091] Comparative Example

[0092] Comparative Example 1

[0093] Preparation of FePO4 nanoparticles: In Comparative Example 1, anhydrous FePO4 nanoparticles were prepared using the same method as in Examples 1 and 2.

[0094] Preparation of lithium manganese iron phosphate (LiMn 0.6 Fe 0.4PO4-S6) positive electrode material: The FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4 and glucose prepared above were weighed to 12.21g, 3.37g, 13.97g, 12.63g and 10.65g respectively, and mixed evenly with 66.54mL of distilled water in a 500mL beaker. Then, the ball-to-material ratio was 15:1 and ball milled at 800rpm for 12h; after ball milling, it was blown dried at 80℃ for 12h and dry milled at 1000rpm for 20min to obtain a precursor sample. The precursor sample was placed in a tube furnace and calcined at 350℃ for 4h under nitrogen atmosphere, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.4 PO4-S6 positive electrode material.

[0095] Figure 7 LiMn in Comparative Example 1 0.6 Fe 0.4 SEM image of PO4-S6 positive electrode material.

[0096] like Figure 7 As shown, the LiMn prepared in Comparative Example 1 0.6 Fe 0.4 The PO4-S6 cathode material particles are evenly distributed and have good dispersion.

[0097] Comparative Example 1: LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.4 PO4-S6 positive electrode sheets were assembled into button batteries for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing processes were the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0098] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.4 The PO4-S6 positive electrode sheet has an initial discharge capacity of 156.15 mAh / g at 0.1C, 151.31 mAh / g at 0.2C, 146.53 mAh / g at 0.5C, 143.46 mAh / g at 1.0C, 138.67 mAh / g at 2.0C, 131.24 mAh / g at 5.0C, and 123.51 mAh / g at 10.0C. 0.6 Fe 0.4The PO4-S6 positive electrode sheet was cycled for 500 cycles at 5.0C, and the battery capacity retention rate was 86.51%; after cycling for 500 cycles at 10.0C, the battery capacity retention rate was 85.35%.

[0099] Comparative Example 2

[0100] FePO4 nanoparticles: FePO4 nanoparticles were synthesized using the method provided in Chinese Patent Publication No. CN114477120A (A method for preparing iron phosphate). Specifically, FePO4 nanoparticles were prepared by adding 25 mL of FeSO4·7H2O solution to a 100 mL reactor, heating to 40°C, stirring at 50 r / min, and adding a flow rate of 13 m 3 / h H3PO4 solution, after 3 hours of reaction, add excess H2O2 solution to the reaction system Fe 2+ Oxidized to Fe 3+ The oxidation reaction was continued for 2 hours. After the reaction, the pH of the reaction system was adjusted to 4.2 with NH3·H2O solution, producing a milky white precipitate. The temperature was then raised to 90°C and stirred for 1.0 hour. After the reaction was complete, the solid was filtered while hot. After filtration, the solid was placed in a 1000mL beaker, 500ml of pure water was added, and stirred with an electric stirrer at 200 rpm for 3 minutes. This was the first filtration and washing. The filtration and washing process was repeated five times. After washing, the solid was transferred to a large glass Petri dish and placed in a forced air drying oven at 60°C. It was then dried at this temperature for 12 hours. Finally, the sample was placed in a quartz boat in a tube furnace and heated in air at a rate of 5°C / min to 550°C. It was then calcined in the tube furnace at this temperature for 3 hours to produce anhydrous FePO4 nanoparticles.

[0101] Figure 8 This is the SEM image of FePO4 nanoparticles in Comparative Example 2.

[0102] like Figure 8 As shown, the FePO4 nanoparticles synthesized by the method in Comparative Example 2 have irregular morphology, uneven particle size distribution, poor dispersibility and serious agglomeration.

[0103] Preparation of lithium manganese iron phosphate (LiMn 0.6 Fe 0.4PO4-S7) Positive electrode material: Weigh the masses of iron phosphate FePO4, Li2CO3, MnCO3, LiH2PO4 and glucose in the above comparative example 2 as 12.21g, 3.37g, 13.97g, 12.63g and 10.65g respectively, and mix them evenly with 66.54mL distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was carried out at 800rpm for 12h; after ball milling, it was blown dried at 80℃ for 12h and dry milled at 1000rpm for 20min to obtain a precursor sample. The precursor sample was calcined at 350℃ for 4h in a tube furnace under nitrogen atmosphere, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.4 PO4-S7 positive electrode material.

[0104] Comparative Example 2: LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.4 The PO4-S7 sample positive electrode sheet was assembled into a button battery for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process was the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0105] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.4 The PO4-S7 positive electrode sheet has an initial discharge capacity of 144.85 mAh / g at 0.1C, 143.05 mAh / g at 0.2C, 141.92 mAh / g at 0.5C, 137.50 mAh / g at 1.0C, 131.15 mAh / g at 2.0C, 118.46 mAh / g at 5.0C, and 101.45 mAh / g at 10.0C. 0.6 Fe 0.4 The PO4-S7 positive electrode sheet was cycled for 500 cycles at 5.0C, and the battery capacity retention rate was 86.00%; after cycling for 500 cycles at 10.0C, the battery capacity retention rate was 82.76%.

[0106] The above-mentioned comparative example 2 adopts a method for preparing FePO4 nanoparticles different from that of Example 1 of the present invention. The differences and advantages between the two are as follows.

[0107] (1) In Example 1, NaOH was used as the precipitant, while in Comparative Example 2, NH3·H2O was used as the precipitant. During the preparation of FePO4 nanoparticles in Comparative Example 2, a large amount of toxic ammonium ions was introduced, causing serious environmental pollution. The subsequent treatment process was relatively complicated and was not suitable for large-scale industrial production.

[0108] (2) In Example 1, NaOH solution was used to adjust the pH of the system to 1.8, while in Comparative Example 2, NH3·H2O solution was used to adjust the pH of the system to 4.2. The use of NH3·H2O solution to adjust the pH of the system is likely to cause some Fe to remain in the system. 3+ And converted into Fe(OH)3 precipitation, namely Fe 3+ The conversion is incomplete.

[0109] (3) The temperature for preparing FePO4 nanoparticles in Example 1 is 80°C. The prepared FePO4 nanoparticles are spherical and regular in shape, with a smooth and delicate particle surface, consistent particle size and uniform dispersion. However, the temperature for preparing FePO4 nanoparticles in Comparative Example 2 is 90°C. Due to the high reaction temperature, the particle size distribution of the prepared FePO4 nanoparticles is uneven, and there is obvious agglomeration.

[0110] Therefore, in the present invention, NaOH is preferably used as a precipitant and pH regulator for preparing FePO4 nanoparticles, and the pH of the system is adjusted to 1.8.

[0111] Comparative Example 3

[0112] Comparative Example 3, referring to Chinese Patent Publication No. CN118231612A, discloses a rare earth element (La, Ce, Pr, Tb, or Sm)-doped lithium iron manganese phosphate / carbon-coated cathode material, its preparation method, and application. La, the element with the best performance, was selected to replace Yb ​​or Eu in the preparation of a lithium iron manganese phosphate cathode material as a comparative example. The only difference is that the doping element in Example 1 is 1% Yb, while the doping element in Comparative Example 3 is 1% La. In other words, Comparative Example 3 provides a lanthanum (La)-doped carbon-coated lithium iron manganese phosphate cathode material, its preparation method, and application. The specific process is as follows.

[0113] Preparation of FePO4 nanoparticles: In Comparative Example 3, anhydrous FePO4 nanoparticles were prepared using the same method as in Examples 1 and 2.

[0114] Preparation of La-doped carbon-coated lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 La 0.01PO4-S8) positive electrode material: FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, La(CH3COO)3·4H2O and glucose were weighed as 11.90g, 3.37g, 13.97g, 12.63g, 0.71g and 10.65g respectively, and then 66.54mL of distilled water was added for mixing, and ball milled at 800rpm for 12h, wherein the ball-to-material ratio was 15:1. Subsequently, it was dried at 80°C to evaporate all the water, and after evaporation, it was dry-milled at 1000rpm for 20min, and the powder was sieved with a 200-mesh standard sieve to obtain a precursor sample. Finally, the precursor powder was placed in a nitrogen atmosphere and calcined at 350°C for 4h; then calcined at 670°C for 12h to obtain LiMn 0.6 Fe 0.39 La 0.01 PO4-S8 positive electrode material.

[0115] Comparative Example 3: LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.39 La 0.01 PO4-S8 positive electrode sheets were assembled into button batteries for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing processes were the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0116] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.39 La 0.01 The PO4-S8 positive electrode sheet has an initial discharge capacity of 146.47 mAh / g at 0.1C, 141.23 mAh / g at 0.2C, 135.03 mAh / g at 0.5C, 128.82 mAh / g at 1.0C, 122.65 mAh / g at 2.0C, 113.15 mAh / g at 5.0C, and 100.59 mAh / g at 10.0C. 0.6 Fe 0.39 La 0.01 The PO4 positive electrode sheet was cycled for 500 cycles at 5.0C, and the battery capacity retention rate was 82.25%; after cycling for 500 cycles at 10.0C, the battery capacity retention rate was 75.67%.

[0117] The difference between Example 1 and Comparative Example 3 is that the hexacoordinated La 3+ The electronegativity of the six-coordinated Yb 3+The electronegativity of La is 1.479, so it can be seen that 3+ The electronegativity is significantly weaker than that of Yb 3+ Therefore, the weakly electronegative La 3+ Mn in MnO6 octahedron 3+ The ability to adjust the chemical environment of the electron cloud and the effect of Mn 3+ The electron accommodation capacity of the outermost local electron cloud is weaker than that of Yb 3+ , and the suppression effect on the Jahn-Teller distortion of lithium manganese iron phosphate is weak, making the 1% La doped 3+ LiMn 0.6 Fe 0.39 La 0.01 The PO4-S8 cathode material does not show a large discharge capacity and good capacity retention at high rate (10.C). 3+ The ionic radius of Fe in the modified lithium manganese iron phosphate cathode material (LMFP) 2+ / 3+ 、Mn 2+ / 3+ The ionic radius of La 3+ The ionic radius of Fe in the modified lithium manganese iron phosphate cathode material (LMFP) is 2 + / 3+ 、Mn 2+ / 3+ The ionic radius of La is about 20pm larger. The large difference in ionic radius leads to the La-doped LiMn 0.6 Fe 0.39 La 0.01 The crystal phase of the PO4-S8 positive electrode material is unstable, and the electrochemical performance and battery cycle stability of the subsequent batteries made using this positive electrode material are poor.

[0118] Comparative Example 4

[0119] Comparative Example 4 uses Tm instead of Yb to prepare a lithium iron manganese phosphate cathode material. The only difference is that the doping element in Example 1 is 1% Yb, while the doping element in Comparative Example 4 is 1% thulium (Tm). This provides a thulium (Tm)-doped carbon-coated lithium iron manganese phosphate cathode material, its preparation method, and application. The specific process is as follows.

[0120] Preparation of FePO4 nanoparticles: In Comparative Example 4, anhydrous FePO4 nanoparticles were prepared using the same method as in Examples 1 and 2.

[0121] Preparation of Tm-doped carbon-coated lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Tm 0.01PO4-S9) positive electrode material: FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Tm(CH3COO)3·4H2O and glucose were weighed as 11.90g, 3.37g, 13.97g, 12.63g, 0.71g and 10.65g respectively, and then 66.54mL of distilled water was added for mixing, and ball milled at 800rpm for 12h, wherein the ball-to-material ratio was 15:1. Subsequently, it was dried at 80°C to evaporate all the water, and after evaporation, it was dry-milled at 1000rpm for 20min, and the powder was sieved with a 200-mesh standard sieve to obtain a precursor sample. Finally, the precursor powder was placed in a nitrogen atmosphere and calcined at 350°C for 4h; then calcined at 670°C for 12h to obtain LiMn 0.6 Fe 0.39 Tm 0.01 PO4-S9 positive electrode material.

[0122] Furthermore, Comparative Example 4 prepared LiMn 0.6 Fe 0.39 Tm 0.01 PO4-S9 positive electrode sheets were assembled into button batteries for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing processes were the same as in Examples 1 and 2.

[0123] After testing, LiMn 0.6 Fe 0.39 Tm 0.01 The PO4-S9 positive electrode sheet has an initial discharge capacity of 145.28 mAh / g at 0.1C, 143.19 mAh / g at 0.2C, 140.84 mAh / g at 0.5C, 136.72 mAh / g at 1.0C, 130.94 mAh / g at 2.0C, 120.78 mAh / g at 5.0C, and 109.26 mAh / g at 10.0C. 0.6 Fe 0.39 Tm 0.01 The PO4 positive electrode sheet was cycled for 500 cycles at 5.0C, and the battery capacity retention rate was 86.83%; after cycling for 500 cycles at 10.0C, the battery capacity retention rate was 80.27%.

[0124] The difference between Example 1 and Comparative Example 4 is that although the six-coordinated Tm 3+ (Tm 2+ Radius 94pm, Tm 3 +Radius 86.9pm); and Yb in the present invention 3+ (Yb 2+ Radius 93pm, Yb 3+ radius 85.8pm) have similar ionic radii, but Tm 3+ There are no unpaired single electrons (4f 12 ), is relatively stable and has a low tendency to absorb external electrons, while the six-coordinated Yb 3+ The outer layer of the electron cloud has an unpaired single electron (4f 13 ), has a high tendency to absorb foreign electrons to achieve a stable full-filled state. In other words, Yb 3+ The outermost electron layer is larger than Tm 3+ The outermost electron layer of the Tm is more inclined to absorb foreign local electrons to achieve a more stable electron layer full filling state. 3+ Mn in MnO6 octahedron 3+ The ability to adjust the chemical environment of the electron cloud and the effect of Mn 3+ The electron accommodation capacity of the outermost local electron cloud is weaker than that of Yb 3+ , and the inhibition effect on the Jahn-Teller distortion of lithium manganese iron phosphate is weak, so that the 1% Tm 3 + LiMn 0.6 Fe 0.39 Tm 0.01 The PO4-S9 cathode material does not show a large discharge capacity and good capacity retention at high rate (10.C). In other words, doping with 1% Yb 3+ It can also reduce or inhibit LiMn 0.6 Fe 0.4-x M x The Jahn-Teller distortion of PO4 cathode material makes LiMn 0.6 Fe 0.4-x M x PO4 cathode material has better performance at high current density.

[0125] Table 1

[0126]

[0127] Table 2

[0128]

[0129] From Table 1 and Table 2 above, it can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01PO4-S1 positive electrode material and LiMn prepared in Example 2 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode material, LiMn prepared in Example 3 0.6 Fe 0.38 Yb 0.02 Comparison of the rate performance of PO4-S3 cathode materials shows that the LiMn 0.6 Fe 0.39 Yb 0.01 The rate performance of PO4-S1 cathode material is the best, so it can be concluded that 1% Yb 3+ The doping amount is optimal.

[0130] From Table 1 and Table 2 above, it can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode material and LiMn prepared in Comparative Example 1 0.6 Fe 0.4 Comparison of the rate performance and long cycle performance of PO4-S6 cathode materials at high rates (5.0C, 10.0C, i.e., high current density): It can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The rate performance and long cycle performance of the PO4-S1 cathode material at high current density are significantly better than those of the LiMn prepared in Comparative Example 1. 0.6 Fe 0.4 PO4-S6 positive electrode material, so 1% Yb 3+ The performance of the doped cathode material at high current density is better than that of the undoped Yb 3+ There is a significant improvement.

[0131] From Table 1 and Table 2 above, it can be seen that the LiMn prepared in Example 5 0.6 Fe 0.39 Yb 0.01 PO4-S5 positive electrode material, and LiMn prepared in Comparative Example 2 0.6 Fe 0.4 The comparison of the rate performance and the long cycle performance of the PO4-S7 cathode material at high rates (5.0C, 10.0C, i.e., high current density) shows that the LiMn prepared in Example 5 0.6 Fe 0.39 Yb 0.01 The rate performance and long cycle performance of the PO4-S5 cathode material at high rates are significantly better than those of the LiMn prepared in Comparative Example 2. 0.6 Fe 0.4PO4-S7 electrode material, so it can also be obtained that 1% Yb is doped 3+ The performance of the electrode material after doping is better than that of the undoped Yb at high current density. 3+ There is a significant improvement.

[0132] From Table 1 and Table 2 above, it can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode material, and LiMn prepared in Comparative Example 1 0.6 Fe 0.4 The PO4-S6 cathode material is used for rate performance and long cycle performance comparison at high rate (5.0C, 10.0C, high current density). It can be seen that although the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The rate performance of the PO4-S1 cathode material at low rate (0.1C-0.5C, i.e. low current density) is inferior to that of the LiMn prepared in Comparative Example 1. 0.6 Fe 0.4 The rate performance of PO4-S6 electrode material is due to the Yb 3+ The ionic radius of Fe in the modified lithium manganese iron phosphate cathode material (LMFP) is 2 + / 3+ 、Mn 2+ / 3+ The ionic radius of Yb is slightly larger, and the smaller radius mismatch leads to the 0.6 Fe 0.39 Yb 0.01 The crystal structure of the PO4 cathode material changes slightly, while at low rates (0.1C-0.5C) LiMn 0.6 Fe 0.39 Yb 0.01 Mn in PO4 positive electrode material 3+ The Jahn-Teller effect is not obvious, so at this time LiMn 0.6 Fe 0.39 Yb 0.01 The properties of the PO4 cathode material itself determine its electrochemical performance, that is, LiMn without Yb doping 0.6 Fe 0.4 PO4-S1 cathode material has a higher discharge specific capacity at low current density; however, at high rate (5.0C, 10.0C, i.e., high current density), the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The discharge capacity and long cycle performance of the PO4-S1 cathode material are better than those of the LiMn prepared in Comparative Example 1. 0.6 Fe 0.4PO4-S6 positive electrode material, this is because LiMn 0.6 Fe 0.4 Mn in PO4-S6 cathode material 3+ The Jahn-Teller effect is significant, and Yb rare earth metal ions are doped. 3+ The outermost electron layer tends to absorb foreign local electrons to achieve a more stable state of half-filled or fully filled electron layer, which changes the MnO6 octahedron 3+ The chemical environment of the electron cloud alleviates or suppresses the LiMn 0.6 Fe 0.4-x M x Jahn-Teller distortion of PO4 cathode material, at this time, the inhibitory effect of Yb rare earth ions on the Jahn-Teller distortion effect is dominant, making LiMn 0.6 Fe 0.4-x M x PO4 cathode material has better performance at high current density.

[0133] From Table 1 and Table 2 above, it can be seen that the LiMn prepared in Comparative Example 1 0.6 Fe 0.4 PO4-S6 positive electrode material and LiMn prepared in Comparative Example 2 0.6 Fe 0.4 The rate performance of PO4-S7 cathode materials is compared. It can be seen that the LiMn prepared in Comparative Example 1 0.6 Fe 0.4 The rate performance of PO4-S6 electrode material is significantly better than that of LiMn prepared in Comparative Example 2. 0.6 Fe 0.4 The PO4-S7 electrode material is attributed to the use of highly dispersed, uniformly spherical FePO4 nanoparticles synthesized by the present invention as a precursor, so that the synthesized modified lithium manganese iron phosphate positive electrode material has more excellent electrochemical performance.

[0134] In summary, the present invention adopts an experimental method without additives, low energy consumption, low temperature (80℃) and simple post-treatment to synthesize spherical FePO4 nanoparticles with high dispersibility, uniform particle size distribution and small particle size, and uses it as a raw material for preparing LiMn 0.6 Fe 0.4-x M x PO4 raw materials. Through the comparison of electrochemical performance, it can be seen that the LiMn prepared later 0.6 Fe 0.4- x M x PO4 cathode material has higher discharge capacity and better rate performance at high rate and high current density.3+ 、Yb 3+ The unique aspherical flexible 4f electron orbital and the outermost electron layer tend to absorb foreign local electrons to achieve a more stable electron layer half-filled or fully filled state, which is used to adjust the MnO6 octahedral Mn in the modified lithium manganese iron phosphate positive electrode material. 3+ The chemical environment of the electron cloud can suppress the LiMn 0.6 Fe 0.4-x M x The Jahn-Teller effect of PO4 reduces the structural distortion of the material and improves its performance.

[0135] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A modified lithium manganese iron phosphate positive electrode material, characterized in that: The modified lithium manganese iron phosphate positive electrode material is a carbon-coated modified lithium manganese iron phosphate, wherein the modified lithium manganese iron phosphate is LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu; the modified lithium manganese iron phosphate has an olivine structure, Fe has a +2 valence state, Mn and M both have a +3 valence state, and the non-spherical flexible 4f electron orbits and the properties of the Yb or Eu rare earth metal ions that tend to absorb external localized electrons are used to adjust the Mn in the MnO6 octahedron 3+ The electrochemical environment of the electron cloud reduces the LiMn 0.6 Fe 0.4-x M x Structural distortion of PO4.

2. A method for preparing the modified lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The method comprises: Providing FePO4 nanoparticles; The solvent, the FePO4 nanoparticles, a lithium source, a manganese source, a phosphorus source, a carbon source and an M source are ball-milled to form a slurry, wherein the M source is a Yb source or a Eu source; The slurry is dried, ground and sieved to obtain powder; The powder is calcined in stages in an inert atmosphere to obtain a modified lithium iron manganese phosphate positive electrode material, wherein the modified lithium iron manganese phosphate positive electrode material is carbon-coated modified lithium iron manganese phosphate.

3. The method according to claim 2, characterized in that The FePO4 nanoparticles are first oxidized by a divalent iron salt and a phosphorus-containing solution under oxidant conditions, and then the pH of the reaction solution is adjusted to 1.5-1.8 with an alkaline solution, and the reaction is carried out for 1-3 hours to obtain a FePO4 slurry. The FePO4 slurry is calcined to obtain FePO4 nanoparticles, wherein the phosphorus-containing solution includes a phosphate solution or a phosphoric acid solution.

4. The method according to claim 2, characterized in that: The lithium source is selected from at least one of Li2CO3, LiOH, LiNO3, LiCl, and CH3COOLi; The manganese source is selected from at least one of MnCO3, Mn3(PO4)2, MnHPO4, Mn(H2PO4)2, Mn(CH3COO)2, Mn(NO3)2, MnSO4, MnC2O4, and MnCl2; The phosphorus source is selected from at least one of H3PO4, Fe3(PO4)2, FePO4, (NH4)2HPO4, NH4H2PO4, (NH4)3PO4, Li3PO4, and LiH2PO4; The carbon source is selected from at least one of glucose, sucrose, fructose, soluble starch, citric acid, amino acids, dextrin, polyvinyl pyrrolidone, and polyethylene glycol; The Yb source is selected from any one of Yb2O3, Yb(CH3COO)3·4H2O, YbCl3, Yb2(SO4)3, and Yb(NO3)3·5H2O; The Eu source is selected from any one of Eu2O3, Eu(CH3COO)3·4H2O, EuCl3, Eu2(SO4)3, and Eu(NO3)3·6H2O; The solvent is water or ethanol.

5. The method according to claim 2, characterized in that: The ball milling mixing time is 6-15 hours, the rotation speed is 600-1000 rpm, and the ball-to-material ratio is 15-20:

1.

6. The method according to claim 5, characterized in that The stepwise calcination of the powder comprises: The powder is first calcined at 300-350° C. for 2-6 hours, and then calcined at 600-750° C. for 10-15 hours.

7. A positive electrode sheet, characterized in that: The positive electrode sheet is composed of a positive electrode current collector and a positive electrode slurry coated and solidified on the positive electrode current collector; The positive electrode slurry comprises the modified lithium manganese iron phosphate positive electrode material as claimed in claim 1, a conductive material, a binder and an organic solvent.

8. The positive electrode sheet according to claim 7, characterized in that: The binder is selected from any one of polyvinylidene fluoride, polystyrene butadiene copolymer, sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, polyamide, polyethylene imine, and polypyrrole; The conductive material is selected from any one of conductive carbon black, acetylene black, Ketjen black, and carbon nanotubes; The organic solvent is selected from any one of N-methylpyrrolidone, dimethylformamide and dimethyl sulfoxide.

9. A lithium ion battery, characterized in that: The lithium-ion battery uses the positive electrode sheet as described in any one of claims 7-8.

Citation Information

Patent Citations

  • Preparation method of iron phosphate

    CN114477120A

  • Rare earth element doped lithium iron manganese phosphate / carbon coated positive electrode material and preparation method and application thereof

    CN118231612A

  • Method for preparing manganese phosphate lithium / carbon composite material

    CN102769131A

  • Nickel-doped lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof

    CN114566646A

  • Preparation method of low-temperature high-dispersity spherical nano iron phosphate

    CN117023537A